Addressing Terms Used in Nathan and Nadia Movie - Siahaan, Desta Gloria; Tefa, Ferawati; Bouk, Edmundus (ICONELT, 2022)
This research tried to obtain the result of analyzing address term in Nathan and Nadia Movie by MD Entertainment. In this research, the researchers used descriptive qualitative method that primarily exploratory research. There are forty-three dialogs that represent all the dialogs inside the movie that represent all the address term. So, the chosen dialogs analized by put them in the table and devided into each part of kind of address term, there are five types of addressing term, they are : using name, using intimacy, using respect, using kinship and using mockery name. the analysis result from this study, The types of addressing term score showed that each types of addressing terms present different score. The types of addressing term commonly used are addressing terms using kinship name 36,59%. Then it is followed by addressing terms using name which presents 24,39% and then followed by addressing term using intimacy present 17,07% and addressing term using mockery name present 17,07%, and the least used is addressing terms using respect name presents 4,88%. The researchers concluded that addressing terms using kinship name is the most and frequently used.